Chlorido(4,4′,4′′-tri-tert-butyl-2,2′:6′,2′′-terpyridine)platinum(II) tetrafluoridoborate - Rami J. Batrice; Vladimir N. Nesterov; Bradley W. Smucker (Acta Crystallographica Section E, 2010)
In the title compound, [PtCl(C27H35N3)]BF4, the PtII atom is in a pseudo-square-planar coordination, which is typical of Pt–terpyridine complexes. The Pt—Cl bond distance is 2.2998 (7) Å. The Pt—N distance of the N atom on the central pyridine is 1.931 (2) Å, while the peripheral N atoms have Pt—N distances of 2.018 (2) and 2.022 (2) Å. The cations pack as dimers in a head-to-tail orientation with an intermolecular Pt...Pt distance of 3.5214 (2) Å and Pt...N distances of 3.527 (2), 3.873 (2) and 4.532 (2) Å. In the crystal, cations and anions are linked by weak C—H...F hydrogen-bonding interactions.